Clinical profile of dengue fever infection in patients admitted in NCMC medical college, Panipat, Haryana, India - Shah, Mohd Younus; Y. Shah, Faisal; Y. Shah, Faizan; Satya, Saurabh (International Journal of Research in Medical Sciences, 2018)
Background: Dengue infections can result in a wide spectrum of disease severity ranging from an influenza-like illness (dengue fever; DF) to the life-threatening dengue hemorrhagic fever (DHF)/dengue shock syndrome (DSS). The study was aimed to compare the clinical profile of all patients diagnosed with dengue viral infection at NCMC. Methods: This retrospective study included 136 patients infected with dengue virus, age 2 years to 68 years. Laboratory and haematological data were included. Results: Peak of infection occurred in Nov. 2017 and least number of cases were recorded in September 2017. Common clinical symptoms were fever, headache and myalgia. Common haematological abnormalities were thrombocytopenia and leucopoenia. All patients survived. There was no case of dengue hemorrhagic fever or dengue shock syndrome. Conclusions: Significant differences in the clinical profile is possibly because of infection with different serotypes of dengue virus (DENV), concurrent/sequential infection of more than one serotype, and differences in host immune responses associated with host genetic variations.